Urban Rainfall-Runoff Study To Validate The Design Chart In The Malaysian Urban Storm Water Management Manual (MSMA). - Abustan, I; Sulaiman, A H; Abdul Wahid, N (2008)
Knowledge on rainfall-runoff response is vital in engineering practices for developing area in the humid tropics. This paper will discuss the runoff response due to varying rainfall within small Malaysian urban catchment.